Laser microprocessing of glass - Chew, Sherman Shi Jie (Nanyang Technological University, 2020)
Borosilicate glass is a commonplace material used in our daily lives. The conventional method of mechanical scribe and break is unsuitable for precision glass processing as it produces uneven edges and requires post processing which prolongs the fabrication process. Ultrashort pulse laser processing will be able to cleanly fracture and achieve tight dimensional tolerances for machining glass due to the kerf-less separation process. The internal modifications induced by a picosecond laser can have a vast applications such as forming waveguides, cutting of glass etc. This project studies (a) the internal damage induced on borosilicate glass by a picosecond pulse laser fitted with a 27 foci multi-foci lens and (b) the effects of surface roughness on laser-glass processing. For (a) the multi-foci lens, with a focusing lens, is used to simultaneously direct the beam at different focal points along the optical axis to modify the glass internally. In contrast to continuous wave laser, an ultrashort pulse laser offers extremely high peak power. As the laser pulse span is in picoseconds which is shorter than the material conduction span, it minimizes the undesirable formation of heat affected zone in glass processing. Through experimental investigations for laser microprocessing using multi-foci, the following results were concluded. (1) Altering the positions of the foci with a multi-foci lens and a 20 mm EFL lens, experiments were effective in having most of the foci within the glass but the foci separations were not consistent. (2) At a low scanning speed of 1 mm/s with a multi foci lens and a 20 mm EFL lens, the laser was able to cause significant damage and evaporate the top surface of the glass. (3) Altering the positions of the foci with a multi-foci lens and a 12 mm EFL lens was not effective in having most of the foci within the glass and the separations between foci were inconsistent. (4) A high scanning speed of 10 mm/s with a 12 mm EFL lens presents clear separation between the foci which was effective in fabricating waveguides, whereas the 0.1 mm/s speed experiment showed overlapping foci which resulted in a straight cut within the cross section of the glass. (5) A low pulse repetition rate of 50 kHz achieved deep damage in the glass, whereas the high pulse repetition rate of 200 kHz did not have sufficient laser fluence to induce any damage in the glass. (6) A laser fitted with a multi foci lens and a 12 mm EFL lens produced a more significant scribe on the surface compared to a 20 mm EFL lens. (7) The variations in the surface roughness of the borosilicate glass in this study were not significant enough to cause a big deviations in the laser effect on the surface. The 1064 nm wavelength, 2.3 W picosecond laser used in this experiment did not have sufficient energy to induce significant damage to separate the glass. Future research to cut borosilicate glass with higher power pulsed laser can be explored. However, using the multi-foci lens presents an effective method to fabricate multiple waveguides within the cross section of the glass. The technique used in this experiment to roughen the surface of borosilicate glass did not prove to be an effective method in enhancing the laser damage induced in the glass. The surfaces with distinctively different roughness values could not be achieved; therefore the difference in roughness was not prominent enough for achieving different laser-material interaction.